A Hybrid Approach for Improving Data Security in Cloud Computing using Greedy DFS Ranked Searching - Joshi, Narendra S.; Sambrekar, Kuldeep P.; Patankar, Abhijeet J; Allagi, Shridhar; Patil, Uttam (International Journal of Intelligent Systems and Applications in Engineering, 2023)
As cloud usage increases daily, security-related issues become more critical. Leakage of personal information when exchanging data via cloud services is a pressing problem. Unauthorized access to the cloud can cause massive blow to any company’s databases. To protect your data the data in the cloud, encryption is needed. But then searching through a large amount of encrypted data itself is a challenge. This review paper explores the previous study done in this area of research. This should enable quickest search, with least possible computing resource requirements, maintain privacy of the data and high speed while searching. Further, certain new objectives are proposed, like implementation of a new encryption algorithm to improve data security in cloud computing using Greedy DFS Ranked Searching. An attempt is given to devise an advance search algorithm for effective time saving technique in cloud system. Hybridization of encryption algorithm is also be explored, and a model for efficient privacy-preservation mechanism with multi-keyword ranked searching algorithm is proposed